2018
DOI: 10.1159/000486916
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated Serum MiR-146b Serves as a Biomarker for Acute Ischemic Stroke

Abstract: Background/Aims: Stroke is a major cerebrovascular disease threatening human health and life with high morbidity, disability and mortality. It is aimed to find effective biomarkers for the early diagnosis on stroke. Methods: The expressions of 17 previously reported strokeassociated miRNAs were measured using quantitative RT-PCR and the expressions of plasma high-sensitivity C reactive protein (hs-CRP) and serum interleukin 6 (IL-6), the proinflammation markers in brain injury, were examined using enzyme-linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…MiRNAs have emerged as important regulators of cardiovascular physiological processes [ 55 ]. It has been documented that miR-21, miR-223 and miR-146b served as biomarkers for acute ischemic stroke [ 17 , 56 , 57 ]. Additionally, elevated serum expression of miR-15a, miR-16 and miR-17-5p was also found to be strongly associated with the AIS [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs have emerged as important regulators of cardiovascular physiological processes [ 55 ]. It has been documented that miR-21, miR-223 and miR-146b served as biomarkers for acute ischemic stroke [ 17 , 56 , 57 ]. Additionally, elevated serum expression of miR-15a, miR-16 and miR-17-5p was also found to be strongly associated with the AIS [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies suggested that changes in miRNA expression in the peripheral blood may be closely associated with the development of AIS, which may be exploited for the development of predictive, diagnostic and prognostic markers for this disease (24,25). miRNAs are single-stranded RNA molecules 18-25 nucleotides in length that regulate gene expression in many cellular processes (2,27). Although the protective role of miR-135b was previously reported in neurons (16,17), the expression pattern and specific role of miR-135b in AIS remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke, which is also known as cerebral infarction, is the sudden deprivation of blood supply in the brain (1). In addition to having 6.1% mortality, stroke is also associated with a high risk of disability and recurrence around the world, accounting for 3% of the total health expenditure (2)(3)(4). This condition is mainly divided into two categories, ischemic stroke and hemorrhagic stroke, of which the former is the most prevalent, accounting for ~80% of total cases (5).…”
Section: Introductionmentioning
confidence: 99%
“…Stoke includes acute ischemic stroke (AIS) and hemorrhagic stroke, with the former being responsible for almost 85% of cases . At present, the diagnosis of AIS primarily relies on laboratory examination and neuroimaging techniques, including computed tomography or magnetic resonance imaging (MRI), digital subtraction angiography (DSA), and transcranial Doppler ultrasound (TCD), among which DSA remains the gold standard for diagnosis of AIS; however, the exorbitant cost and invasiveness are not suitable for all patients . Although several techniques are available for diagnosing AIS, the early ischemic changes in the brain of AIS patients cannot usually be detected, thus the prognosis of patients remains unsatisfactory due to the delay of diagnosis .…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA ANRIL, a newly documented antisense noncoding RNA at the INK4 locus, plays a role in the atherosclerotic processes such as thrombogenesis and vascular remodeling and/or repair and in plaque stability and inflammatory responses . In the pathogenesis of AIS, atherosclerosis and inflammatory responses are identified as two of the most crucial pathogenetic factors for development and progression of cerebral arterial occlusion . However, the correlation of lncRNA ANRIL expression with stroke risk and severity, as well as inflammatory cytokines levels in AIS patients is still not well documented.…”
Section: Introductionmentioning
confidence: 99%